Individualized CT image-guided free-hand catheter technique: A new and reliable method for minimally invasive evacuation of basal ganglia hematoma - Zhao, Zhijie; Xiao, Jinting; Wang, Jianjun; Meng, Xiangjing; Li, Cuiling; Xin, Tao; Li, Shengjie (Frontiers in Neuroscience, 2022)
OBJECTIVE To validate the clinical reliability of an individualized CT image-guided free-hand catheter technique (CTGFC) for basal ganglia hematoma (BGH) evacuation. METHODS From January 2017 to December 2020, 58 cases of patient with BGH who underwent catheter evacuation were enrolled. The surgery was conducted by CTGFC (n = 31) or stereotactic catheter technique (STC, n = 27) respectively. Authors evaluated the baseline characteristics, operation-related indicators, postoperative complications, hospitalization-related indicators, short-term and long-term functional outcomes, and mortality rate 1 year after surgery. RESULTS All patients underwent BGH evacuation under non-general anesthesia in the CTGFC group. The operative time (p<0.01) and operation costs (p<0.05) were significantly shorter in the CTGFC group than that in the STC group (p<0.01). Comparable results were found in the catheter indwelling duration, residual hematoma volume, hematoma evacuation rate, incidence of postoperative complications, hospital ICU stay and hospital costs between these two groups (p>0.05). The duration of hospital stay was remarkable shorter in the CTGFC group than that in the STC group (p<0.01). There were no differences in terms of the short-time functional outcomes score at discharge including the glasgow outcome scale (GOS) score, activities of daily living (ADL) score, and karnofsky performance score (KPS). Moreover, comparable findings were also found in the 1-year postoperative GOS score, ADL score, KPS score and mortality rate between these two groups. CONCLUSIONS The simple CTGFC-assisted surgery was a safe and reliable option for BGH evacuation especially in primary medical institutes and emergency situations with limited medical resources.